The use of advanced sensory techniques to describe the petit suisse profile (Research, Society and Development, 2020)
The conventional descriptive methodologies show a long duration time of the sensory technique, once they require extensive training of the tasters. As a way of decrease these problems, new methodologies has been developed allowing to obtain sensory information of the products in shorter times, due these methodologies can be done without a previous training. Among these new sensory methodologies can be named the RATA test (Rate All That Apply), a variation of the CATA test (Check All That Apply), in which the costumer is requested to indicate if the points at a list can be applied to describe the product and if yes qualify its intensity. The aim of this research was to evaluate the preference and investigate the sensory profiles of four brands of petit suisse by the CATA method and its variation RATA through a non-trained panel (n=100), comparing these two methodologies. For this purpose, two approaches of different analysis were followed, treating data as frequencies, typical of the CATA test, and evaluation of the attribute intensity, typical of the RATA test. Simultaneously was performed a ordination-preference test to verify the preference among the samples. The results showed that the RATA approach resulted in higher discriminatory capacity in comparison to the CATA approach. The Sample PS2 showed the lower levels of intensity for all evaluated attributes except for the desoraling attribute. The brand PS1 was significantly different (p